1999
DOI: 10.1007/s005860050204
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal static imbalance in myelomeningocele patients: improvement in sitting ability by partial and total gibbus resection

Abstract: IntroductionThe myelomeningocele (MMC) is one of the dysraphic disorders of the neural arch. Pathogenically it is caused by the absence of proliferation of neuroectodermal cells after migration is finished. The occult form without neurologic deficit is estimated to have incidence of up to 1%, while a spina bifida aperta cystica with everted myelon and complete paraplegia occurs in 0.005% of live births. With the help of postnatal closure of the sac and the early commencement of hydrocephalus therapy, the life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
1
16
2
4
Order By: Relevance
“…This is especially important in the MMC population in which patients frequently have comorbid illnesses. The only exception to our lower operative time was Furderer's study of 14 patients in which his operative time was 216 minutes; however, his blood loss was 1194 mL as compared with the mean of 765 mL in our study [6] . Estimated blood loss in other series of patients ranged from 155 mL to 3000 mL (Table 3).…”
Section: -Inchcontrasting
confidence: 82%
See 4 more Smart Citations
“…This is especially important in the MMC population in which patients frequently have comorbid illnesses. The only exception to our lower operative time was Furderer's study of 14 patients in which his operative time was 216 minutes; however, his blood loss was 1194 mL as compared with the mean of 765 mL in our study [6] . Estimated blood loss in other series of patients ranged from 155 mL to 3000 mL (Table 3).…”
Section: -Inchcontrasting
confidence: 82%
“…Estimated blood loss in other series of patients ranged from 155 mL to 3000 mL (Table 3). Despite a couple of outliers [4,30], the remainder of studies reported blood loss greater than 800 mL [6,20,22,27,28,32]. Longer operative times and the extent of distal exposure in their techniques likely resulted in greater blood loss.…”
Section: -Inchmentioning
confidence: 99%
See 3 more Smart Citations